ANALYSIS OF LEADING ECONOMIC SECTORS OF SOPPENG REGENCY, SOUTH SULAWESI PROVINCE - Rasulong, Ismail; Zaimuddin, Muhammad (Perpustakaan dan Penerbitan Unismuh Makassar, 2020)
This study aims to determine the shifting economic structure and find out the leading sektors in Soppeng Regency in 2013-2017. The type of research used is quantitative research. The data processed is the data of the Gross Regional Domestic Product (GRDP) of Soppeng Regency and South Sulawesi Province on the basis of constant prices in 2010 in 2013-2017 in all sectors. The data analysis technique used to determine the shift in economic structure and leading sektors in Soppeng District is Location Quotient (LQ) Analysis, Shift Share (SS) Analysis and Klassen Typology analysis. The results of the Location Quotient (LQ) analysis show the agriculture, forestry and fisheries sectors; electricity and gas procurement sectors; construction; trade and repair of cars and motorbikes; providing accommodation and drinking meals; real estate; government administration, defense and social security; education services; and health services and social activities are the leading sectors in Soppeng Regency. The result of Shift Share analysis shows that the sector experiencing a shift is the processing industri sector; trade and repair of cars and motorbikes; providing accommodation and drinking meals; information and communication; financial services; health services and social activities; and other services with PB> 0. While the Klassen Typology analysis shows that the advanced and fast-growing sektors are agriculture, forestry and fisheries; and real estate.